Designing Virtual Ethnophysics Kekehan on Moment of Inertia and Angular Momentum: Analyzing Students' Creative Thinking Skills - Adrian Bagas Damarsha; Nadi Suprapto; Eko Hariyono; Elisa Dwi Yuliatin; Joenathan Eka Prasetya; Mita Sofita; Husni Mubarok; Septian Rahman Hakim; Alif Syaiful Adam (Jurnal Pemberdayaan Masyarakat, 2026)
Creative thinking skills are fundamental to education, so a strategy to improve them in line with the current era is needed. Therefore, there needs to be a combination of improving creative thinking skills with learning grounded in culture and humanism. This study aims to describe creative thinking skills, learning needs, media design, and media validity. This study used a development design with a 3D scheme (Define, Design, Development). Data collection was conducted through observation, design, and validity testing. The results showed that students' creative thinking skills were low. Additionally, in physics, students still require visualizations of the concepts presented. Furthermore, the observation results revealed that students support the media development. This posed a challenge for researchers in developing SiVEKa (Simulasi Virtual Ethnophsyics Kekehan). In the media design process, the researcher based the design on student observations and the relevant learning theory. The validity results indicated that the SiVEKa media was highly valid, enabling further testing. In addition, this study contributes to preserving culture through learning. This study hopes to contribute to learning using ethno-integrated technology.